Aetiology of chronic liver disease is a valuable factor for stratifying adverse outcomes of acute decompensation: prospective observational study - Kim, Jung Hee; Kim, Sung-Eun; Song, Do Seon; Kim, Hee Yeon; Yoon, Eileen L.; Park, Ji Won; Kim, Tae Hyung; Jung, Young-Kul; Suk, Ki Tae; Yim, Hyung Joon; Kwon, Jung Hyun; Lee, Sung Won; et al. (Annals of medicine (Helsinki), 2025)
Acute decompensation (AD) is defined as the development of complications related to portal hypertension and liver dysfunction that affect the progression of chronic liver disease (CLD) or liver cirrhosis (LC). Variations exist in patient demographics and prognostic outcomes of AD based on the aetiology of CLD, encompassing LC. However, limited research has been conducted to analyse these discrepancies across aetiologies. The prospective Korean Acute-on-Chronic Liver Failure (KACLiF) cohort consisted of 1,501 patients who were hospitalized with AD of CLD from July 2015 to August 2018. In this study, we assess the clinical attributes and prognostic implications of AD with CLD/LC stratified by the aetiology. Among 1,501 patients, the mean age was 54.7 years old and 1,118 patients (74.5%) were men. The common events of AD were GI bleeding (35.3%) and jaundice (35.0%). There was a median follow-up of 8.0 months (1.0-16.0 months). The most common aetiology of CLD was alcohol ( = 1021), followed by viral hepatitis ( = 206), viral hepatitis with alcohol-related ( = 129), cryptogenic ( = 108) and autoimmune ( = 37). Viral hepatitis with alcohol-related CLD showed a poor liver function profile and a high frequency of acute-on-chronic liver failure (ACLF) [22.1% vs. 19.6% (alcohol CLD), 8.1% (viral CLD), 5.6% (autoimmune related CLD and 16.0% (cryptogenic CLD)] with worse adverse outcomes (mortality or liver transplantation) than other aetiologies. The difference in aetiology was a significant factor for 28-day adverse outcomes in multivariate analysis even in a high MELD score (≥15), which indicated poor baseline liver function and prognosis ( < 0.001). The aetiology of CLD constitutes a pivotal determinant influencing both short- and long-term adverse outcomes of AD in CLD, even among individuals presenting with elevated MELD scores. Notably, patients afflicted with viral hepatitis should exercise caution even in the consumption of modest quantities of alcohol that induced the exacerbations in the adverse outcomes associated with AD.